2014
DOI: 10.1007/s11746-014-2529-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functional Evaluation of Soy Fatty Acid Methyl Ester Ketals as Bioplasticizers

Abstract: A facile synthesis of the soy fatty acid methyl ester ketal has been accomplished using acetone in the presence of catalytic anhydrous ferric chloride starting from commercially available soy biodiesel (soy fatty acid methyl ester) after evaluating various synthetic procedures. The soy ketal product was fully characterized by nuclear magnetic resonance, infra‐red and chromatography. The physical and analytical properties of soy ketal as determined by thermogravimetric analysis, viscosity acid and saponificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Compared with the nanoparticles with no rutin ( Table 1 ), the particle size decreased significantly (P < 0.05). This could have occurred because the rutin affected the crystalline state of the aggregated particles [ 28 ]. Rutin acts as a plasticizer between zein-SC nanoparticles, and when a lower quantity of rutin was added, the zein nanoparticles were more uniform and stable and were smaller.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the nanoparticles with no rutin ( Table 1 ), the particle size decreased significantly (P < 0.05). This could have occurred because the rutin affected the crystalline state of the aggregated particles [ 28 ]. Rutin acts as a plasticizer between zein-SC nanoparticles, and when a lower quantity of rutin was added, the zein nanoparticles were more uniform and stable and were smaller.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Kandula et al (2014) showed that fatty acid methyl ester ketals derived from soybean oil can be synthesized via the epoxide as intermediates. The synthesized soy ketal compounded with PVC exhibited better thickening and aging behaviors as compared to petroleum-based plasticizers.…”
Section: Stabilizer/plasticizer For Rubber and Pvcmentioning
confidence: 99%
“…Triacylglycerols, obtained not only from vegetable origin, but also from animal sources, in fact, represent one of the cheapest and most available starting materials for replacing petroleum-derived products. Their derivatives found successful application in niche domains, such as lubricants for total-loss applications [4,5], plastifying agents for food-grade products [6,7] or intermediates for pharmaceutical uses [8,9]. However, in order to attain an appropriate degree of sustainability of the overall process and to properly tackle the fuel vs. food/feed biomass dilemma, the scientific community is paying an ever-increasing attention to oleochemicals derived from either non-edible oils, extracted from land-or water-saving crops, or animal fats, obtained from food-processing waste [10][11][12].…”
Section: Introductionmentioning
confidence: 99%